Genital porokeratosis: A report of two cases and review of literature - Rakesh P Roge; Sumit A Hajare; Jayesh I Mukhi; Rajesh P Singh (Wolters Kluwer Medknow Publications, 2020)
Porokeratosis (PK) is an uncommon disorder of keratinization that presents with keratotic papules or annular plaques that expand centrifugally with a thread-like elevated border. Genital involvement in PK is a rare occurrence even in disseminated forms. We encountered two patients who had PK primarily affecting the genital area. Both cases were males out of which one case had involvement of the scrotum and thigh and other case had only scrotal involvement. The cases were difficult to diagnose clinically, but dermoscopy was helpful and was further confirmed on histopathology.